Current State and Prospects of Development of the Sports System of Ukraine: Legal Aspects - Ткалич, Максим Олегович; Ткалич, М. О.; Tkalych, Maxym О.; Давидова, Ірина Віталіївна; Давидова, І. В.; Давыдова, Ирина Витальевна; Davydova, Iryna V.; Толмачевська, Юлія Олегівна; Толмачевська, Ю. О.; Толмачевская, Юлия Олеговна; Tolmachevska, Yuliia O. (San Javier, 2020)
The article analyzes the current state of the sports organization system in Ukraine. The authors of the article argue that thesports system in Ukraine needs to be reformed in light of current trends in world sports. First and foremost, the need for regulatory andinstitutional development of the professional sport, which can have a positive impact on the development of the entire sports systemof Ukraine. Currently, the dominant position in Ukrainian sport is occupied by the state and non-governmental organizations. Thisapproach was justified under the conditions of a planned economy during the Soviet Union, but it is now outdated and hinders thedevelopment of Ukrainian sport.Instead, modern sport in developed countries is primarily driven by private initiative and the creationof appropriate conditions for a variety of private law entities to promote entrepreneurial activity in sport. The purpose of the article isto identify the key institutional and legal factors of the domestic sports system that negatively affect its development. Adequateregulatory support for commercial sports will give additional funds in domestic sports, which inevitably plays a role in improving sportsachievements and restoring Ukraine’s position in the world sports arena. The key direction of the development of domestic sports theauthor sees the further commercialization and professionalization of domestic sports. The authors of the article state that the Ukrainianlegislature should as soon as possible turn its attention to the normative provision of sports, in particular - to adopt a number ofamendments to the current law «On physical culture and sports» or to adopt a new law on sports and/or the law «On professional sports».
Tkalych M. Current State and Prospects of Development of the Sports System of Ukraine: Legal Aspects (Estado actual y perspectivas de desarrollo del sistema deportivo de Ucrania: aspectos legales) / M. Tkalych, I. Davydova, Yu. Tolmachevska // Retos. – N. 38(38). – San Javier, 2020. – P. 385-389.
Keywords: commercial sports; legal regulation of sports; participants of sports-legal relations; professional sports; regulatory supportof sports; комерційний спорт; правове регулювання спорту; учасники спортивно-правових відносин; професійний спорт; регулятивна підтримка спорту; коммерческий спорт; правовое регулирование спорта; участники спортивно-правовых отношений; профессиональный спорт; нормативное обеспечение спорта; Research Subject Categories::LAW/JURISPRUDENCE